1994
DOI: 10.1111/j.1651-2227.1994.tb12943.x
|View full text |Cite
|
Sign up to set email alerts
|

Cells, bilirubin and light: formation of bilirubin photoproducts and cellular damage at defined wavelengths

Abstract: Cultured cells from one human and one murine cell line were treated with bilirubin and irradiated with visible light of different wavelengths, either from phototherapy lamps or from a Xenon/Mercury lamp equipped with a monochromator. Bilirubin bound to human serum albumin was also irradiated with light. After irradiation, the bilirubin and its photoisomers were extracted and analysed with High Pressure Liquid Chromatography. The formation of single strand breaks in the DNA of treated cells was studied using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
2

Year Published

1997
1997
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
22
1
2
Order By: Relevance
“…22 It was suggested that green light exposure favors the production of lumirubin, while blue light causes more DNA damage and cytotoxicity. 23 However, more recent in vitro studies demonstrated that green fluorescent phototherapy of hyperbilirubinemia may also cause both skin and immune system damage. 19 At present, it remains to be proven whether genotoxic effects observed have clinical implications and if they occur when LED light is used.…”
Section: Discussionmentioning
confidence: 99%
“…22 It was suggested that green light exposure favors the production of lumirubin, while blue light causes more DNA damage and cytotoxicity. 23 However, more recent in vitro studies demonstrated that green fluorescent phototherapy of hyperbilirubinemia may also cause both skin and immune system damage. 19 At present, it remains to be proven whether genotoxic effects observed have clinical implications and if they occur when LED light is used.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with respect to effectiveness, the turquoise light had no advantage over the blue light. However, potential side effects may be less serious in phototherapy with longer wavelengths: in cell cultures containing bilirubin, turquoise light caused less DNA damage (12) and was less cytotoxic (13), compared with blue light. Furthermore, during phototherapy with blue light, the serum level of riboflavin decreased due to photodecomposition (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been thought for a long time that phototherapy and bilirubin, as a factor of increasing light sensitivity, might have harmful effects on DNA and some previous studies showed these effects. Christensen et al (14) and Wu et al (15) showed increased cytotoxicity and DNA damage in newborn lymphocytes that were exposed to blue light especially. Similar to our study, Karadag et al (16) reported that both enhanced and conventional phototherapy increased the frequency of SCE.…”
Section: Discussionmentioning
confidence: 99%